Folk theorems for present-biased players - Axel Bernergård (Stockholm School of Economics, The Economic Research Institute (EFI), 2011)
The folk theorems for infinitely repeated games with discounting presume that the discount rate between two successive periods is constant. Following the literature on quasi-exponential or hyperbolic discounting, I model the repeated interaction between two or more decision makers in a way that allows present-biased discounting where the discount factor between two successive periods increases with the waiting time until the periods are reached. I generalize Fudenberg and Maskin's (1986) and Abreu, Dutta and Smith's (1994) folk theorems for repeated games with discounting so that they apply when discounting is present-biased. Patience is then represented either by the discount factor between the next and the current period or, alternatively, by the sum of the discount factors for all future periods.
Keywords: C73; 330; folk theorem; present-biased; discounting; hyperbolic; Wiederholte Spiele; Zeitkonsistenz; Folk-Theorem; Spieltheorie